On the Mechanisms of Biliary Flux. Issue 6 (25th September 2021) - Vartak, Nachiket; Drasdo, Dirk; Geisler, Fabian; Itoh, Tohru; P.J.Oude Elferink, Ronald; van de Graaf, Stan F.J.; Chiang, John; Keitel, Verena; Trauner, Michael; Jansen, Peter; Hengstler, Jan G.
Abstract : Since the late 1950s, transport of bile in the liver has been described by the "osmotic concept, " according to which bile flows into the canaliculi toward the ducts, countercurrent to the blood flow in the sinusoids. However, because of the small size of canaliculi, it was so far impossible to observe, let alone to quantify this process. Still, "osmotic canalicular flow" was a sufficient and plausible explanation for the clearance characteristics of a wide variety of choleretic compounds excreted in bile. Imaging techniques have now been established that allow direct flux analysis in bile canaliculi of the intact liver in living organisms. In contrast to the prevailing osmotic concept these analyses strongly suggest that the transport of small molecules in canalicular bile is diffusion dominated, while canalicular flow is negligibly small. In contrast, with the same experimental approach, it could be shown that in the interlobular ducts, diffusion is augmented by flow. Thus, bile canaliculi can be compared to a standing water zone that is connected to a river. The seemingly subtle difference between diffusion and flow is of relevance for therapy of a wide range of liver diseases including cholestasis and NAFLD. Here, we incorporated the latest findings on canalicular solute transport, and align them with extant knowledge to present an integrated and explanatory framework of bile flux that will undoubtedly be refined further in the future.